Heritage of the sea famous preserved ships around the UK - Smith, Peter C. (Pen & Sword Maritime, 2012)
During the period from Sir Francis Drake to the 21st century the naval power of Great Britain rose from that of an obscure island to that of a world-wide empire. This book lists all the major vessels, from the Museum ships to the exhibitions and replicas all of them evoke pride and diversity and invite study from all age-groups. The ships and their proud histories are described in detail, along with details of how they may be visited and enjoyed.